An Analysis of Language Style in Lord Byron's Poem 'She Walks in Beauty' with a Romantic Approach - Desvita Aulia Wulan; Aisyah Ayu Pratiwi (STIKes Ibnu Sina Ajibarang, 2025)
This piece looks at the use of figure speech, mainly images and giving human traits to things, in Lord Byron's poem 'She Walks in Beauty' from the view of Romanticism. The study shows that B͏yron uses these writing tools to show a woman's beauty in a soft and heartfelt way while also sharing his love and respect for her. This look into it points out how these style choices matter in building meaning and feeling within the poem's setting, stressing ideas of true beauty emotion someone being unique, and creative thought.